2017
DOI: 10.3847/1538-4357/835/1/85
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Magnetic Helicity in Structuring the Solar Corona

Abstract: Two of the most widely observed and yet most puzzling features of the Sun's magnetic field are coronal loops that are smooth and laminar and prominences/filaments that are strongly sheared. These two features would seem to be quite unrelated in that the loops are near their minimumenergy current-free state, whereas filaments are regions of high magnetic stress and intense electric currents. We argue that, in fact, these two features are inextricably linked in that both are due to a single process: the injectio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 43 publications
0
28
0
Order By: Relevance
“…If these effective vortical motions are mainly counterclockwise/ clockwise in the northern/southern hemisphere, then the resultant helicity injection is negative/positive, leading to dextral/sinistral filament channels. High-resolution numerical simulations (Knizhnik et al 2015(Knizhnik et al , 2017aZhao et al 2015) have confirmed the accumulation of helicity at the perimeter of a compact region of such vortical flows in a plane-parallel corona, supporting the validity of the three-stage process described above. In a more definitive study of helicity condensation, in a bipolar magnetic region with a true PIL at the solar surface, Knizhnik et al (2017b) formed a filament channel having concentrated shear and dipped field lines, as observed on the Sun.…”
Section: Introductionmentioning
confidence: 52%
“…If these effective vortical motions are mainly counterclockwise/ clockwise in the northern/southern hemisphere, then the resultant helicity injection is negative/positive, leading to dextral/sinistral filament channels. High-resolution numerical simulations (Knizhnik et al 2015(Knizhnik et al , 2017aZhao et al 2015) have confirmed the accumulation of helicity at the perimeter of a compact region of such vortical flows in a plane-parallel corona, supporting the validity of the three-stage process described above. In a more definitive study of helicity condensation, in a bipolar magnetic region with a true PIL at the solar surface, Knizhnik et al (2017b) formed a filament channel having concentrated shear and dipped field lines, as observed on the Sun.…”
Section: Introductionmentioning
confidence: 52%
“…Current sheet formation can arise as the magnetic field becomes increasingly complicated by the action of photospheric motions, and spontaneous magnetic reconnection results in the breaking and reformation of field lines in a more stable, lower-energy configuration. Examples of such studies can be found in Galsgaard & Nordlund (1996), De Moortel & Galsgaard (2006), O'Hara & De Moortel (2016, and Knizhnik et al (2017). Ritchie et al (2016) demonstrate the significance of the nature of the driving motions, with the associated helicity and topological entropy, for the scale and frequency of heating events.…”
Section: Introductionmentioning
confidence: 93%
“…This conjecture has been tested numerically (Zhao 2015;Knizhnik et al 2015Knizhnik et al , 2017, but only within a simplified Parker (1972) coronal model, which consists of an initially uniform 7 vertical field between two horizontal planes that represent the photosphere. Small-scale flows on these planes were used to inject free energy and helicity into the system.…”
Section: Introductionmentioning
confidence: 99%